2016
DOI: 10.1007/s12199-016-0548-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of attention deficit hyperactivity disorder and/or autism spectrum disorder and its relation to lifestyle in female college students

Abstract: The prevalence of suspected ADHD and/or ASD may be relatively high even among female college students in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…However, when excluding the study of Takahashi et al (2016), adolescents with ADHD experienced significantly more insomnia than TD adolescents. Publication bias was not assessed as a limited number of studies were included.…”
Section: Risk Of Bias and Publication Biasmentioning
confidence: 86%
“…However, when excluding the study of Takahashi et al (2016), adolescents with ADHD experienced significantly more insomnia than TD adolescents. Publication bias was not assessed as a limited number of studies were included.…”
Section: Risk Of Bias and Publication Biasmentioning
confidence: 86%
“…The prevalence of autism is recently increasing (Weintraub, 2011), and both ASD and ADHD are frequently found even in college students (Takahashi et al, 2016). Although the causes of autism have not been fully elucidated, both genetic and environmental factors affect pathogenesis and deterioration (Weintraub, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both ASD and attention-deficit hyperactivity disorder (ADHD) are frequently found in college students (Takahashi et al, 2016). Students experiencing such problems, particularly those with ASD, frequently feel isolated and many have a lifetime history of suicidal behaviors (Jackson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While research on assessment with this specific population is limited, in a study conducted by Katz et al (2009), participants self-reported higher childhood and current symptoms scores than informants. Studies that conducted among university students generally used 6 item ASRS for screening probable ADHD, and the rate of students who were classified as "probable", "highly likely" or "suspected ADHD" were 8.3% (Mortier et al, 2015), 13.4% in online version (Burlison et al, 2013) and 27.2% (Takahashi et al, 2016) respectively. Finally, both the 6-item and 18-item ASRS are feasible, reliable and cost efficient approaches to use in the assessment and monitoring of ADHD symptoms in the university population (Gray et al, 2014).…”
Section: Adult Adhd Self-report Scales (Asrs-v11)mentioning
confidence: 99%